Research on the Glial–Lymphatic System and Its Relationship With Alzheimer’s Disease - Ding, Danhua; Wang, Xinyu; Li, Qianqian; Li, Lanjun; Wu, Jun (Frontiers in Neuroscience, 2021)
Metabolic waste clearance is essential to maintain body homeostasis, in which the lymphatic system plays a vital role. Conversely, in recent years, studies have identified the glial-lymphatic system in the brain, which primarily comprises the inflow of fluid along the para-arterial space. Aquaporin-4 mediates the convection of interstitial fluid in the brain and outflow along the paravenous space. β-Amyloid deposition is a characteristic pathological change in Alzheimer's disease, and some studies have found that the glial-lymphatic system plays an important role in its clearance. Thus, the glial-lymphatic system may influence Alzheimer's disease severity and outcome; therefore, this review summarizes the current and available research on the glial-lymphatic system and Alzheimer's disease.